Comparative effectiveness of oral anticoagulants in venous thromboembolism: GARFIELD-VTE. Issue 191 (July 2020) - Bounameaux, Henri; Haas, Sylvia; Farjat, Alfredo E.; Ageno, Walter; Weitz, Jeffrey I.; Goldhaber, Samuel Z.; Turpie, Alexander G.G.; Goto, Shinya; Angchaisuksiri, Pantep; Nielsen, Joern Dalsgaard; Kayani, Gloria; Schellong, Sebastian; et al.
Abstract: Introduction: Randomized controlled trials have shown that direct oral anticoagulants (DOACs) are a safe and effective alternative to vitamin K antagonists (VKAs) for the treatment of venous thromboembolism (VTE). However, there are limited post-marketing data describing the effectiveness and safety of the DOACs in the community setting. We aimed to compare the effectiveness of DOACs and VKAs on 12-month outcomes in a real-world VTE patient population. Methods: The Global Anticoagulant Registry in the FIELD (GARFIELD)-VTE is an observational study designed to document real-world treatment practices. This intention-to-treat analysis included 7987 VTE patients initiated on either DOACs (N = 4791) or VKAs (N = 3196) with or without pre-treatment with parenteral anticoagulants. Treatment groups were balanced according to baseline characteristics, using overlapping propensity score weights. Results: After adjustment for baseline characteristics, all-cause mortality was significantly lower with DOAC than with VKAs (hazard ratio [HR]: 0.73; 95% confidence interval [CI] 0.56–0.95. Patients receiving VKAs were more likely than those receiving DOACs to die of complications of VTE (4.7% vs 2.7%) or from bleeding (4.2% vs. 1.3%). There was no significant difference in recurrent VTE (HR: 0.91, 95% CI 0.71–1.18), major bleeding (HR 1.03, 95% CI 0.69–1.54), or overall bleeding (HR 0.96, 95% CI 0.81–1.14) with DOACs or VKAs. Conclusions: In this real-world analysis of VTE treatment, DOACs were associated with reduced all-cause mortality compared with VKAs, and similar rates of recurrent VTE and bleeding. Highlights: This study compared the effectiveness of DOACs and VKAs in a real-world VTE setting DOACs were associated with reduced all-cause mortality compared with VKAs Patients receiving VKAs were more likely to die of VTE, or from bleeding The rates of recurrent VTE and bleeding were comparable between treatment groups